Process Practice for the Self-lubricating Bush of C2082H-RP Maintenance-free Feeder Machine Chain - Zhang Yuan; Zhang Yi (Jixie chuandong)
The iglidur bearing self- lubricating bush which used in C2082H-RP maintenance-free feeder machine chain is described,and process analysis on iglidur bearing is carried out. The analysis shows,this kind of iglidur bearing self- lubricating bush has the properties of low noise,oil- free operation,long life span and maintenance- free,can meet the demand of hygiene standard for the feeder machine chain in tobacco industry.